Rarity of synovitis in polymyalgia rheumatica. Issue 3 (March 1990) - Kyle, V; Tudor, J; Wraight, E P; Gresham, G A; Hazleman, B L
Abstract : The joints of 56 patients with polymyalgia rheumatica were examined for evidence of inflammatory synovitis. x Rays, isotope scans, and thermography supplemented clinical examination. Control sternoclavicular joints were examined at necropsy. Peripheral and axial synovitis were uncommon and the results contrast with the findings of several recent studies.